CREATING AN EFFICIENT TAX ADMINISTRATION MECHANISM IN THE DIGITAL ECONOMY - Aripova Aziza Alisherovna (Ecominds Press, 2025)
The article scientifically substantiates the essence and features of tax control in the context of modifying the relationship between tax authorities and taxpayers at the present stage of economic liberalization and modernization of the tax system in the Republic of Uzbekistan.
Keywords: Digital economy, Tax system, tax administration, tax regulation, tax payer.